2001
DOI: 10.1046/j.0022-202x.2001.01402.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of rab7 as a Melanosome-Associated Protein Involved in the Intracellular Transport of Tyrosinase-Related Protein 1

Abstract: The melanosome is a unique secretory granule of the melanocyte in which melanin pigments are synthesized by tyrosinase gene family glycoproteins. Melanogenesis is a highly regulated process because of its inherent toxicity. An understanding of the various regulatory mechanisms is important in delineating the pathophysiology involved in pigmentary disorders and melanoma. We have purified and analyzed the total melanosomal proteins from B16 mouse melanoma tumors in order to identify new proteins that may be invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 80 publications
(81 reference statements)
1
37
0
Order By: Relevance
“…From this point of view, it is very interesting that Rab38, which belongs to the RabRP1 cluster in the Rab-phylogenetic tree, is exclusively localized in cultured melanocytes (Jager et al, 2000). In addition, Rab7, a member of the subfamily neighboring on the RabRP1 cluster, is also localized on melanosomes (Gomez et al, 2001). These results suggest that RABRP1 and its relatives function in the vesicle transport pathways for pigment-containing organelles, both in insects and mammals.…”
Section: A Possible Function Of Rabrp1mentioning
confidence: 68%
“…From this point of view, it is very interesting that Rab38, which belongs to the RabRP1 cluster in the Rab-phylogenetic tree, is exclusively localized in cultured melanocytes (Jager et al, 2000). In addition, Rab7, a member of the subfamily neighboring on the RabRP1 cluster, is also localized on melanosomes (Gomez et al, 2001). These results suggest that RABRP1 and its relatives function in the vesicle transport pathways for pigment-containing organelles, both in insects and mammals.…”
Section: A Possible Function Of Rabrp1mentioning
confidence: 68%
“…4A). Rab7 is a small GTPase regulator of lysosome (Bucci et al 2000;Meresse et al 1995;Vitelli et al 1997), late endosome (Feng et al 1995) and melanosome trafficking (Gomez et al 2001). ARPE-19 cells transfected with a wildtype version of Rab7 fused to the green fluorescent protein (GFP-Rab7wt) were stained for myosin-VIIa and, similar to the colocation seen with cathepsin D antibodies, the majority of the myosin-VIIa-positive vesicles were decorated with GFP-Rab7wt (Fig.…”
Section: Localization Of Myosin-viia To Lysosomes Is Rab7 Independentmentioning
confidence: 75%
“…While Rab27a was shown to participate in melanosome transport and its defect leads to a clustering of melanin pigment in the hair shaft as well as defective melanosome transport in the melanocyte (Wu et al 1998;Menasche et al 2000;Wilson et al 2000;Bahadoran et al 2001), a dominant negative mutant of Rab27b has recently been shown to disrupt melanosomal movement (Chen et al 2002). However, the localization of Rab8, though identified in melanosomes by immunoblotting, has not yet been characterized functionally (Gomez et al 2001). Based on known effects of Rab8 on vesicular traffic between the trans-Golgi network (TGN) and the basolateral plasma membrane in different cell types including hippocampal neurons (Huber et al 1993a(Huber et al , 1993bFischer et al 1994;Mohrmann and van der Sluijs 1999), it can be speculated that Rab8 might have a role in melanocytes for melanosome secretion.…”
Section: Introductionmentioning
confidence: 95%
“…Of the five Rab proteins, Rab7, Rab3a, Rab8, Rab27a, and Rab27b have so far been identified as being associated with or present in melanosomes (Araki et al 2000;Scott and Zhao 2001;Gomez et al 2001;Bahadoran et al 2001;Hume et al 2001), and Rab7 has been implicated in the transport of tyrosinase-related protein 1 (TRP-1) through the Golgi stack to the melanosome (Gomez et al 1996(Gomez et al , 2001. Rab3A has been suggested to play a role with SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptors) in targeting melanosomes to the plasma membrane, transfer of melanosomes to keratinocytes, or both (Scott and Zhao 2001).…”
Section: Introductionmentioning
confidence: 99%